Solid state interfacial reaction of Sn-3.5Ag solders with Ni-P and Ni-W-P under bump metallization - Zhang, Keran (2016)
(Ni-P and Ni-W-P) were developed as the soldering metallization in this work to solve the potential reliability. The interfacial reactions between lead-free Sn-3.5Ag solder and these ternary metallizations during reflow and thermal aging were investigated. The interfacial reaction between the same solder and electrolessly-plated binary Ni-P metallization was compared to understand the effect of the addition of the ternary element. During the metallization, Ni-P is consumed at the faster rate while compared to Ni-W-P. During the Ni-P/Sn-3.5Ag interfacial reaction, as predicted based on the limited available information on the Ni-P phase diagram, the formation of Ni3P is formed. Scattered cracking occurs in Ni3P and Ni3Sn4 metallization layers. Though the overall consumption rate of the Ni-P metallization is slow, the presence of scattered cracking leads to fast degradation of the Ni-P/Sn-3.5Ag solder joint strength. In the case of Ni-W-P, two IMCs, Ni3Sn4 and (Ni,W)3P are formed. No voids are found at the reaction interface after prolonged reaction. The amorphous nature of the (Ni,W)3P layer makes it an effective diffusion barrier for Ni, resulting in the slowest thickness reduction for Ni-W-P metallization. The growths of both Ni3Sn4 and (Ni,W)3P layers are found to be diffusion-controlled. The activation energies for the growth of Ni3Sn4 and (Ni,W)3P layers during solid-state reaction are determined to be 62.3 kJ/mol and 58.2 kJ/mol, respectively.